A pedagogical strategy addressing an unmet need: Making the biology of aging an accessible part of interdisciplinary gerontology education. Issue 1 (2nd January 2019) - Waters, David J.; Hyner, Gerald C.; Ferraro, Kenneth F.
ABSTRACT: In an age of specialization, obstacles to interdisciplinary training and integrated intellectual growth are expected. One such obstacle to graduate-level training in gerontology is the challenge of making the biology of aging accessible to nonbiologists. In this article, the authors' aim is to share 15 years of experience developing a pedagogical strategy that situates the biology of aging as an accessible part of interdisciplinary gerontology education for nonbiologists and biologists alike. The approach hinges on a four-pronged learning opportunity—four course offerings—that places high priority on exactitude with language and sees development of an attitude of precision with language as essential to intellectual growth. By inspiring students to master language in the key of B — B iology of Aging—we unleash a versatile method for developing cross-disciplinary discoverers prepared for a lifetime of seeing and reporting.